ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA ANGGOTA DITLANTAS KEPOLISIAN DAERAH NTT - John EHJ FoEh; Eliana Papote (Universitas Multimedia Nusantara, 2021)
Abstract- The research objectives were to determine: 1) The description of performance, organizational culture, education and training, competence and work motivation of Indonesian National Police members at the Traffic Directorate of East Nusa Tenggara Regional Police; 2) The influence of organizational culture, education and training, competence and work motivation on the performance of Police members at the East Nusa Tenggara Regional Police Traffic Directorate. The study was conducted on all members of the East Nusa Tenggara Police Traffic Directorate with 145 respondents. The data collected were analyzed descriptively based on the results of processed data using the method of Structural Equation Model. The results of descriptive analysis showed that the achievement of the indicators for each variable is as follows: Performance = 67.68 (Good Enough), Organizational Culture = 68.84 (Good), Competence = 67.93 (Good Enough), Education and Training = 67.45 (Good Enough), and Work Motivation = 68.55 (Good). Furthermore, the results of SEM analysis showed that Organizational Culture, Education and Training, Competence and Work Motivation had a positive and significant effect on the Performance of the investigated Police Members. This research is still limited to the 4 variables used so that testing is needed on other variables such as; leadership style, compensation, work atmosphere, work facilities and others with job satisfaction as an intervening variable. Keywords: Performance; Organizational Culture; Education and Training; Competence; Work Motivation